Prevalence of Long COVID-19 and its Impact on Quality of Life Among Outpatients With Mild COVID-19 Disease at Tertiary Care Center in North India. (August 2022) - Sarda, Radhika; Kumar, Arvind; Chandra, Ankit; Bir, Megha; Kumar, Sanchit; Soneja, Manish; Sinha, Sanjeev; Wig, Naveet
Literature is lacking on the spectrum of symptoms of long COVID-19 (defined as symptoms persisting beyond 28 days of diagnosis) and its impact on quality of life. This single-center, cross-sectional study included mild COVID-19 cases as determined by a positive real-time reverse transcription polymerase chain reaction test. Patients were contacted at least 28 days after diagnosis and were interviewed telephonically using semi-structured questionnaires for duration of symptoms, fatigue using Fatigue Severity Scale (FSS) and quality of life using the World Health Organization Quality of Life: Brief Version (WHOQOL-BREF). A total of 251 COVID-19 patients were included; of which 169 (67.3%) were males. The mean age of the patients was 35.8 years (SD = 12.5). The prevalence of long COVID-19 was 28.2% (n = 71, 95% CI: 23.0–34.2). The most common symptoms involved the musculoskeletal system (12.7%), upper respiratory tract (7.6%), and fatigue among 17 (6.8%) patients. Patients with long COVID-19 had significantly higher FSS score and lower WHOQOL-BREF score compared to the patients without long COVID-19 (<28 days).